Variable seismic anisotropy across the Peruvian flat-slab subduction zone with implications for upper plate deformation. (March 2021) - Condori, Cristobal; França, George S.; Tavera, Hernando J.; Eakin, Caroline M.; Lynner, Colton; Beck, Susan L.; Villegas-Lanza, Juan C.
Abstract: We performed shear wave splitting analyses to investigate seismic anisotropy across the northern extent of the Peruvian flat-slab subduction region. We used core-mantle refracted SKS, SKKS and PKS phases from teleseismic events (88° > Δ < 150°) recorded at 45 broadband seismic stations from the Peruvian permanent and portable seismic networks as well as from, international networks (CTBTO, RSBR-Brazil, and RENSIG-Ecuador). The results reveal a complex anisotropy pattern with distinct variations in shear wave splitting along strike. In the northernmost region, the mean delay times range between 1.0 ± 0.2 s and 1.5 ± 0.2 s with fast directions predominantly oriented ENE-WSW approximately perpendicular to the trench, parallel with the motion of the subducting Nazca plate. In the central region of Peru, the predominant fast directions change to a SE-NW orientation that is oblique with the trench. These fast splitting directions are consistent with the pattern seen previously over the southern extent of the flat-slab and correlate well with the current geodetically derived motion of the overriding forearc, the Peruvian Sliver. These characteristics suggest a fundamental change in anisotropic behavior between the northern and central portions of the Peruvian flat-slab and imply that the upper plate deformation is a controlling factor. Highlights: SWS observations reveal two distinct patterns of seismic anisotropy beneath the northern and central Peruvian flat-slab. In central Peru coherence with the Peruvian forearc sliver motion from GPS data implies significant upper plate deformation. In northern Peru SWS appears to primarily reflect deeper mantle flow entrained with the subducting Nazca slab.